Privatization in Africa: What has happened? What is to be done? - John Nellis (Fondazione Eni Enrico Mattei (FEEM), 2005)
Sub-Saharan African states urgently need expanded and more dynamic private sectors, more efficient and effective infrastructure/utility provision, and increased investment from both domestic and foreign sources. Privatization is one way to address these problems. But African states have generally been slow and reluctant privatizers; a good percentage of industrial/manufacturing and most infrastructure still remains in state hands. Given prevailing public hostility towards privatization, and widespread institutional weaknesses, such caution is defensible, but nonetheless very costly. The long-run and difficult solution is the creation and reinforcement of the institutions that underpin and guide proper market operations. In the interim, African governments and donors have little choice but to continue to experiment with the use of externally supplied substitutes for gaps in local regulatory and legal systems.
Keywords: F3; L3; N17; N27; N47; N77; O55; 330; Privatization; Sub-Saharan Africa; Privatisierung; Afrika südlich der Sahara